Contemporary social studies : an essential reader - Russell, William B. (Teaching and learning social studies., 2011)
The field of social studies is unique and complex. It is challenged by the differing perspectives related to the definition, goals, content, and purpose of social studies.Contemporary Social Studies: An Essential Reader discusses the contemporary issues surrounding social studies education today. Contemporary Social Studies: An Essential Reader encourages and inspires readers to think. The chapters included in this volume are written by prominent scholars in the field of social studies. The collection inspires and provokes readers to reconsider and reexamine social studies and its contemporary state. Readers will explore the various critical topics that encompass contemporary social studies.This collection provides readers with rich chapters which are sure to be cited as key works. Compelling and accessible, this collection brings to light the critical topics relevant to contemporary social studies and is sure to serve as a cornerstone and seminal text for the future.